Great transitions in Donaumoos land reclamation (Bavaria, Germany) since the late 18th century – a palaeohydrological and historical perspective - C. Zielhofer; C. Zielhofer; M. Kaniecki; A. Köhler; V. Seeburg; A. Rollo; A. Rollo; L. Bergmann; S. Berg; B. Stammel; B. Stammel; R. Gudermann; et al. (Eiszeitalter und Gegenwart)
Systematic human intervention in wetlands has been taking place in central Europe for several centuries. The Donaumoos fen in Upper Bavaria, Germany, has been cultivated since 1788, resulting in the permanent loss of its natural state. The adjacent Danube River was straightened during the same period. This study presents a quantitative reconstruction over a 235-year-long time frame of the development of the natural Donaumoos fen and Danube River into a human-dominated landscape (anthroposphere). The selected quantitative proxies for the change in the socio-ecological system are the Donaumoos drainage ditch lengths and changes in Danube surface water area traced through the analysis of old maps. A multi-temporal series of old maps from 1788 to 2023 are used to document land reclamation in the Donaumoos and hydro-engineering activities in the Danube floodplain. A comparison of the quantitative data on the development of drainage ditch lengths with the state of research from written sources leads to the discovery of potential great transitions in floodplain and peatland changes and associated human drivers as well as consequences for society in the region. One phase of great transition with far-reaching human interventions spanned 1788 to 1794 and a second phase ran from 1907 to 1959. However, the phases of substantial transitions with river straightening, land reclamation and colonization were embedded in multi-decadal intervals of setbacks and socio-ecological stagnation. Regarding the future, an updated economic and ecological understanding of resources is difficult to implement for the Donaumoos because socio-ecological path dependencies present challenges for the sustainable development of the Donaumoos, in particular, the ongoing and self-reinforcing mechanism of peat subsidence in parallel with the ongoing pressure for drainage under continued agricultural use of the former fen.